2021
DOI: 10.1111/pirs.12578
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration networks, geography and innovation: Local and national embeddedness

Abstract: The relationship between collaboration, geography and innovation has been analysed in economic geography. However, little is known from a social‐network perspective about whether different geographical levels of embeddedness may determine the way networks affect innovation. To address this issue, we compare the effects of regional vs. country‐level Spanish networks on future patenting. If we consider the country‐wide network, our statistical analysis reproduces the findings of the previous literature. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
(152 reference statements)
0
10
0
1
Order By: Relevance
“…Creating links with cognitively distant actors is crucial for (radical) innovations and the acquisition of new knowledge. Some previous works have found that density is negatively correlated with overall innovation (Galaso & Kovářík, 2021; Innocenti et al, 2020). This could be also expected for breakthrough innovations where too much density of the network could impede knowledge transfer and exchange also for radical inventions.…”
Section: Inventors’ Network Diversity and Regional Inventionmentioning
confidence: 91%
“…Creating links with cognitively distant actors is crucial for (radical) innovations and the acquisition of new knowledge. Some previous works have found that density is negatively correlated with overall innovation (Galaso & Kovářík, 2021; Innocenti et al, 2020). This could be also expected for breakthrough innovations where too much density of the network could impede knowledge transfer and exchange also for radical inventions.…”
Section: Inventors’ Network Diversity and Regional Inventionmentioning
confidence: 91%
“…At this point, as the intensity of TDF increases, the firms in the clique can devote more energy to conducting innovation in the sub-clique and share knowledge with clique partners outside the sub-clique. But this good situation is destroyed by GP because firms in cliques have to divert some of their efforts to maintain relationships with geographically proximate firms, which may result in relationship redundancy and even local knowledge homogenization [38][39], thus impeding innovation. After all, GP weakens the positive correlation between low TDF and CIP.…”
Section: B the Moderating Effect Of Geographical Proximitymentioning
confidence: 99%
“…As the intensity of TDF increases, the sub-clique becomes more closed and there is less knowledge flow within the clique, which is negative for innovation. It can be inferred that there is a negative correlation between the intensity of TDF and CIP [37] [38]. In combination with the influence of GP, the geographical closeness between firms within a clique and other firms reduces the cost of cooperation and promotes the flow of knowledge.…”
Section: B the Moderating Effect Of Geographical Proximitymentioning
confidence: 99%
See 1 more Smart Citation
“…We then explore inventors' collaboration patterns by following a social network analysis (SNA) approach, as the structure of research collaborations can be viewed as a network composed of links and nodes (Galaso & Kovářík, 2021). In particular, we investigate whether highways regional endowment favors regional embeddedness into a wider interregional innovation network, as proxied by different measures of node centrality (e.g., Wanzenböck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%